Penalaran Istiṣlāḥī dalam Kajian Fikih Kontemporer: Studi Kasus Fatwa Hukum Imunisasi di Aceh - Husni Mubarrak (Universitas Islam Negeri Jakarta, 2017)
This article discusses the use of istiṣlāḥi reasoning to answer the contemporary problem such as the MPU's Decree (Majelis Permusyawaratan Ulama) in Aceh on immunization.The reasoning of Islamic law often used to answer contemporary problems is the istiṣlāḥi reasoning. Although thei stiṣlāḥiy reasoning is more flexible in explaining the law of contemporary issues, but in the process of law enforcement, it must be assisted with other disciplines. As a result, the legal considerations are decided more accurately and scientifically to avoid any form of arbitrariness (authoritarian) in producing Islamic law. DOI: 10.15408/ajis.v17i1.6225